Needs analysis on task-based English for occupational purposes model: A case of English for civil engineering in Bali State polytechnic - Ardika, I Wayan Dana; Padmadewi, Ni Nyoman; Putra, I Nyoman Adi Jaya; Ratminingsih, Ni Made (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the criteria for a task-based English for Occupational Purposes model at Bali State Polytechnic's Civil Engineering Department. The current English syllabus does not match the civil engineering industry's particular communicative and professional criteria. Thus, a needs analysis was conducted using a descriptive qualitative approach, combining surveys and interviews with instructors, students, and course coordinators, and analyzing the curricular materials. Data was analyzed in three stages: reduction, display, and conclusion drawing. The results revealed flaws in the current curriculum, including outdated pedagogical methods, poor use of discipline-specific terminology, lack of student-centered events, and insufficient instructional tools. Students showed inadequate mastery of basic English skills, particularly in completing assignments related to their disciplines. Moreover, teachers and students understood how unsuccessful traditional teaching strategies were, including passive lectures and inadequately used peer evaluations. These shortcomings highlight the need for a more contextualized, interactive, and task-oriented English learning strategy. It concludes that a task-based English curriculum, including real-world engineering projects, varied learning materials, and group activities, will better meet students' academic and professional needs. Thus, the institution should review and change the syllabi by including industry-relevant capabilities to enable students to communicate in English effectively.